Water-based alkyl ketene dimer ink for user-friendly patterning in paper microfluidics - Nurul Nadiah, Hamidon; Hong, Yumiao; Salentijn, Gert IJ.; Verpoorte, Elisabeth (Elsevier Ltd, 2018)
We propose the use of water-based alkyl ketene dimer (AKD) ink for fast and user-friendly patterning of paper microfluidic devices either manually or using an inexpensive XY-plotter. The ink was produced by dissolving hydrophobic AKD in chloroform and emulsifying the solution in water. The emulsification was performed in a warm water bath, which led to an increased rate of the evaporation of chloroform. Subsequent cooling led to the final product, an aqueous suspension of fine AKD particles. The effects of surfactant and AKD concentrations, emulsification procedure, and cooling approach on final ink properties are presented, along with an optimized protocol for its formulation. This hydrophobic agent was applied onto paper using a plotter pen, after which the paper was heated to allow spreading of AKD molecules and chemical bonding with cellulose. A paper surface patterned with the ink (10 g L−1 AKD) yielded a contact angle of 135.6° for water. Unlike organic solvent-based solutions of AKD, this AKD ink does not require a fume hood for its use. Moreover, it is compatible with plastic patterning tools, due to the effective removal of chloroform in the production process to less than 2% of the total volume. Furthermore, this water-based ink is easy to prepare and use. Finally, the AKD ink can also be used for the fabrication of so-called selectively permeable barriers for use in paper microfluidic networks. These are barriers that stop the flow of water through paper, but are permeable to solvents with lower surface energies. We applied the AKD ink to confine and preconcentrate sample on paper, and demonstrated the use of this approach to achieve higher detection sensitivities in paper spray ionization-mass spectrometry (PSI-MS). Our patterning approach can be employed outside of the analytical lab or machine workshop for fast prototyping and small-scale production of paper-based analytical tools, for use in limited-resource labs or in the field.